Energy-based Options for Male Facial Rejuvenation - Mandavia, Rishi; Sahonta, Elizabeth; Shahidi, Sepideh; Mandavia, Tatiana (Facial Plastic Surgery, 2025)
In recent years, the advancements of minimally invasive, energy-based facial treatments have been followed by an increase in male patient's demand. This article presents a review of current energy-based devices for male facial rejuvenation, aiming to inform clinicians on evidence-based treatment options.A search of the scientific literature in the PubMed database from inception to June 2025 was conducted. Articles were included if they discussed energy-based options for male facial rejuvenation. Out of 70 articles screened, 23 met the inclusion criteria. In included articles, 18 energy-based options used for male facial rejuvenation were reported.This review provides an overview of the wide array of energy-based devices available for male facial rejuvenation. The literature suggests that these technologies can be effectively and safely used to tighten skin, improve contouring while reducing adiposity, enhance skin quality and tone, and manage cosmetic vascular lesions.
Keywords: energy-based devices; minimally invasive; non-surgical; male; skin rejuvenation